2023
DOI: 10.1007/s10900-023-01249-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating COVID-19 Risk to Essential Workers by Occupational Group: A Case Study in Massachusetts

Abstract: Occupational exposure to SARS-CoV-2 varies by profession, but “essential workers” are often considered in aggregate in COVID-19 models. This aggregation complicates efforts to understand risks to specific types of workers or industries and target interventions, specifically towards non-healthcare workers. We used census tract-resolution American Community Survey data to develop novel essential worker categories among the occupations designated as COVID-19 Essential Services in Massachusetts. Census tract-reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…A more balanced approach partitions the population into high-risk and low-risk groups based on their exposure risk, tailoring testing strategies accordingly. The high-risk group includes symptomatic individuals, healthcare workers, and essential workers (Haley et al, 2023). RT-qPCR or similar technologies like RT-LAMP testing is crucial for this group to prevent superspreading events.…”
Section: Introductionmentioning
confidence: 99%
“…A more balanced approach partitions the population into high-risk and low-risk groups based on their exposure risk, tailoring testing strategies accordingly. The high-risk group includes symptomatic individuals, healthcare workers, and essential workers (Haley et al, 2023). RT-qPCR or similar technologies like RT-LAMP testing is crucial for this group to prevent superspreading events.…”
Section: Introductionmentioning
confidence: 99%
“…Occupational and residential segregation, racial capitalism (1), mass incarceration (2) and other manifestations of social and economic inequity (3) have been definitively shown to drive of racial and socioeconomic inequities in infection, severe disease, and death from a wide variety of infections including SARS-CoV-2 (4,5), seasonal and pandemic influenza (6), tuberculosis (7,8), STIs (9) and many others.…”
Section: Introductionmentioning
confidence: 99%
“…40,41 In the early months of the pandemic, studies found higher rates of COVID-19 in Massachusetts communities with greater percentages of workers in essential services, many of whom were likely unable to telework. 42,43 An analysis by Hawkins et al 22 of Massachusetts death certificate data from March-July 2020 found that COVID-19 ageadjusted mortality rates among workers aged 18-64 years varied by occupation group, with 11 groups having higher than average rates. The authors posited that one potential reason for the elevated rates in some groups was that they were more likely to have to work on-site rather than being able to telework, putting them at risk of occupational exposure.…”
mentioning
confidence: 99%